(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
A high Population today relies on instant noodles for their breakfast, lunch and dinner. This study sort to evaluate the effect of instant noodles formulated with Natural spice and that prepared with noodle seasoning on some biochemical parameters. Fifty four (54) Wistar rats were divided into 9 different groups of 6 rats each, Group 1 was control group served with rat pellet and tap water, while groups 2 to 9 served as the treatment groups and were fed differently prepared instant noodles and rat pellet. All the biochemical parameters were analyzed using standard methods. There were no significant difference (P>0.05) in all lipid parameters in groups fed with instant noodles prepared with noodle seasoning compared with the control and the group with Natural spice. Also, in both Total and direct bilirubin the groups fed with instant noodles prepared with noodle seasoning both 80 % and 50 % indicated no significant increases (P< 0.05). The activities of AST, ALT, and ALP rats in groups fed with instant noodles prepared with noodle seasoning increased significantly (p< 0.05) (23.00±1.97) , (31.96±2.09 ) when compared to groups that consumed instant noodles cooked with Natural spice ( 40g crayfish and 30g of onions) compared with the normal control group respectively. This confirmed the hepatotoxic effect of instant noodles cooked with the noodle seasoning that shows a negative impact on the activities of liver enzymes but cooking with Natural spice seems to ameliorate the effect of free radicals deposited on the spices.